Evaluation of anal carcinoma screening in male and female HIV patients at an interdisciplinary HIV therapy centre. (29th April 2019) - Todorova, A.; Schwierzeck, V.; Turek, D.; Zink, A.; Schwerdtfeger, C.; Kaliebe, K.; Spinner, C.D.; Traidl‐Hoffmann, C.
Abstract: Background: Incidence of anal carcinoma is increased in people living with HIV (PLWH). Due to the improved life expectancy in PLWH, identifying appropriate prevention strategies for non‐AIDS‐defining cancer types such as anal carcinoma has become a priority in managing PLWH today. Objective: We aimed to evaluate anal cytology assessment as screening tool for anal dysplasia and/or carcinoma in PLWH, regardless of gender or sexual orientation. Additionally, we investigated the correlation between cancer risk factors and abnormal screening results in our patient cohort. Methods: People living with HIV from the Interdisciplinary HIV Centre of the University Hospital rechts der Isar in Munich, Germany (IZAR), were screened for anal carcinoma by single cytobrush examination and anal Papanicolaou (PAP) smear assessment from 2013 to 2015. Patients with abnormal PAP smear result were offered a follow‐up examination after 12 months. Differences between two groups were tested for statistical significance using Student's t ‐test and Mann–Whitney U ‐test, as appropriate. Results: In total, 101 PLWH were included. 26.7% of subjects ( n = 27) were PAP IIID, and 9.9% ( n = 10) were PAP IVa. Seven female subjects had an abnormal finding at screening. Smoking was significantly associated with abnormal findings at screening ( P = 0.005). In addition, our study found an association between sexually transmitted infections (STI) and anal dysplasia. Condylomata acuminata were increased in subjects with PAP IIID/PAP IVa ( P = 0.045). Reactive syphilis serology was found to be significantly associated with abnormal screening results ( P = 0.016), respectively. Conclusion: Our results demonstrate that smoking and two common STIs, condylomata acuminata and syphilis, are risk factors associated with advanced anal intraepithelial neoplasia (AIN) stages in our PLWH cohort. While further analysis is needed to determine diagnostic guidelines concerning AIN in PLWH, these results suggest that interdisciplinary lifestyle prevention strategies are required to reduce the risk factors for AIN in PLWH in an outpatient setting.